Pengaruh Pemberian Pupuk Organik Cair (POC) Daun Papaya ( Carica papaya L. ) terhadap Pertumbuhan Tanaman Cabai Rawit ( Capsicum fritescens L.) - Adi Saputri, Reni; Sudiarti, Diah; Bukhori, Imam (JURNAL AGROPLANT, 2025)
Cayenne pepper (Capsicum frutescens L.) is one of the horticultural crops that is widely cultivated by farmers because of its great demand by the community, not only in the household but also for industrial purposes and for export abroad. Cayenne pepper contains quite a lot of nutrients and quite a lot of benefits. The purpose of this study was to determine the effect of liquid organic fertilizer (POC) on papaya leaves (C. papaya) on the growth of cayenne pepper (C. frutescens). The study used a completely randomized design with three treatments namely liquid organic fertilizer (POC), positive control (K+) and negative control (K-). Each treatment was carried out in quadruples. The results of the ANOVA test with cayenne pepper showed: 1) the average value of plant height was 0.045; 2) the significance value of the number of leaves is 0.038; 3) The significance value is 0.273 for the number of branches. It can be concluded that the application of papaya leaves (POC) has a significant effect on cayenne pepper (C. frutescens) which has a very good value compared to the use of chemical fertilizers (NPK), so it is continued in the Duncan test experiment. The results of the Duncan test for cayenne pepper plant height showed that the POC treatment had a significant effect on plant height and number of leaves compared to the negative control (k-) and positive control (k+). This is due to the addition of organic matter from fermented cow urine and papaya leaves as well as nutrients in the soil, which can be beneficial both for the soil and for plants.